2020
DOI: 10.1007/s00430-020-00671-5
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD9 affects HPV16 infection by modulating ADAM17 activity and the ERK signalling pathway

Abstract: Human papillomaviruses (HPV) are causative agents of various tumours such as cervical cancer. HPV binding to the cell surface of keratinocytes leads to virus endocytosis at tetraspanin enriched microdomains. Complex interactions of the capsid proteins with host proteins as well as ADAM17-dependent ERK1/2 signal transduction enable the entry platform assembly of the oncogenic HPV type 16. Here, we studied the importance of tetraspanin CD9, also known as TSPAN29, in HPV16 infection of different epithelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…EVs were isolated from FBS-free conditioned media of Colo-320, Colo-320/CD9 and Colo-320/ADAM17-KO cells, by a protocol that included two sequential centrifugations, first at 300× g to discard whole cells and large cellular debris, and at 10,000× g to discard the pellet containing particulate material and larger extracellular vesicles such as microvesicles. The resultant supernatants were [ 20 ] concentrated by tangential flow and spin filtrations and EVs purified by size−exclusion chromatography (SEC) fractionation in a 30 mL Sepharose Fast-Flow 4 column ( Figure 1 A and described in detail in Materials and Methods). Typically, a total of 70 fractions (0.5 mL each) were collected from each sample and their protein content was quantified using the Micro BCA Protein Assay Kit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs were isolated from FBS-free conditioned media of Colo-320, Colo-320/CD9 and Colo-320/ADAM17-KO cells, by a protocol that included two sequential centrifugations, first at 300× g to discard whole cells and large cellular debris, and at 10,000× g to discard the pellet containing particulate material and larger extracellular vesicles such as microvesicles. The resultant supernatants were [ 20 ] concentrated by tangential flow and spin filtrations and EVs purified by size−exclusion chromatography (SEC) fractionation in a 30 mL Sepharose Fast-Flow 4 column ( Figure 1 A and described in detail in Materials and Methods). Typically, a total of 70 fractions (0.5 mL each) were collected from each sample and their protein content was quantified using the Micro BCA Protein Assay Kit.…”
Section: Resultsmentioning
confidence: 99%
“…Our group showed that the tetraspanin CD9 negatively regulated integrin α5β1-mediated adhesion of cancer cells both to its canonical ligand fibronectin and to ADAM17 as a novel ligand [ 14 , 15 ]. Furthermore, we and others have reported that CD9 interacts directly with ADAM17 on the cell surface and regulates negatively both the sheddase and adhesive activities of this metalloproteinase [ 12 , 13 , 14 , 15 , 19 , 20 , 21 ]. Therefore, we decided to investigate whether integrin α5β1 and ADAM17 interaction and the regulatory effects of CD9 also played a role in mediating the binding of exosomes and their uptake by cancer or mesothelial recipient cells, which could bear relevance during the peritoneal dissemination of colorectal carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…CD63 is required for intracellular trafficking of the virus and, therefore, is also a key player in the HPV infection process [15,18,19], whereas CD81 plays a less prominent role [15,19]. Tetraspanin CD9 (TSPAN29), which associates with proviral factors such as ADAM proteases [20,21], seems to play an indirect role in HPV16 entry [21].…”
Section: Introductionmentioning
confidence: 99%
“…Tetraspanins interact with multiple host membrane factors required in this process, collaborating in viral entry, assembly or egress steps [2][3][4][5]. For example, CD9 and CD81 regulate virus-cell membrane fusion in human immunodeficiency virus type I (HIV-1) infection [6]; CD81 facilitates Hepatitis C virus (HCV) entry in cells [7,8]; different tetraspanins regulate entry of papilloma and cytomegalovirus [9,10]; and TEMs are the budding sites for Influenza A virus (IAV) [11] and Herpes simplex virus 1 (HSV-1) [12].…”
Section: Introductionmentioning
confidence: 99%